Conversion of Methionine to Cysteine in Lactobacillus paracasei Depends on the Highly Mobile cysK-ctl-cysE Gene Cluster - Wüthrich, Daniel; Irmler, Stefan; Berthoud, Hélène; Guggenbühl, Barbara; Eugster, Elisabeth; Bruggmann, Rémy (Frontiers in Microbiology, 2018)
Milk and dairy products are rich in nutrients and are therefore habitats for various microbiomes. However, the composition of nutrients can be quite diverse, in particular among the sulfur containing amino acids. In milk, methionine is present in a 25-fold higher abundance than cysteine. Interestingly, a fraction of strains of the species L. paracasei – a flavor-enhancing adjunct culture species – can grow in medium with methionine as the sole sulfur source. In this study, we focus on genomic and evolutionary aspects of sulfur dependence in L. paracasei strains. From 24 selected L. paracasei strains, 16 strains can grow in medium with methionine as sole sulfur source. We sequenced these strains to perform gene-trait matching. We found that one gene cluster – consisting of a cysteine synthase, a cystathionine lyase, and a serine acetyltransferase – is present in all strains that grow in medium with methionine as sole sulfur source. In contrast, strains that depend on other sulfur sources do not have this gene cluster. We expanded the study and searched for this gene cluster in other species and detected it in the genomes of many bacteria species used in the food production. The comparison to these species showed that two different versions of the gene cluster exist in L. paracasei which were likely gained in two distinct events of horizontal gene transfer. Additionally, the comparison of 62 L. paracasei genomes and the two versions of the gene cluster revealed that this gene cluster is mobile within the species.